Pelatihan Pembuatan Kit Praktikum Fisika Berbasis Mikrokontroler Arduino Uno di SMK Negeri 9 Muaro Jambi - Restianingsih, Tika; Nurhidayah, Nurhidayah; Pebralia, Jesi; Anggraini, Rista Mutia (Fakultas Sains dan Teknologi, Universitas Jambi, 2023)
Arduino uno microcontroller is an open source based integrated circuit device that can be easily obtained, relatively cheap, accessible, and low power consumption. It can be applied to design practicum kits related to electronics and electricity. Our community service activity was holding a workshop on making practicum kits based on the Arduino Uno microcontroller for teachers at SMK Negeri 9 Muaro Jambi. The program was carried out through three stages, firstly, observation and survey, next was planning and preparation, and the last one was training. The themes of the chosen practicum kits were the LED turning-on program, distance measuring program, fire detection program, and temperature and humidity measurement. Each of the kits was equipped with the sets needed for practicum, such as Arduino Uno, jumper cables, LEDs, breadboard/protoboard, resistors, USB cables, sensors, etc. The practicum guide book contained the objectives of the practicum, tools and materials used, programming language commands to be uploaded, as well as work steps and evaluations. Workshop was carried out by a lecture about arduino uno microcontroller and demonstration of how to operate practicum kits. During the demonstration activity, the teachers were enthusiastically discussed and asked questions about Arduino Uno microcontroller as a practicum kit.